Critical Incidents and the Impact of Satisfaction on Customer Share - van Doorn, Jenny; Verhoef, Peter C. (Journal of Marketing, 2008)
In business markets, the long-term nature of relationships may prompt parties to conduct “business as usual,” but negative critical incidents (CIs) can cause a destabilization of these long-term relationships. The authors develop a comprehensive dynamic model of customer loyalty to account for the impact of negative CIs on both the nature and the magnitude of the relationships between satisfaction and customer share. The results indicate that CIs trigger a stronger updating of the customer relationship, which moves customers from a business-as-usual mind-set to a reconsideration of the relationship. Furthermore, nonlinearities in the relationships are much more pronounced in the presence of CIs. Depending on the relationship quality, CIs have different consequences for customer relationships, and if relationship quality is high, a negative CI can even have a positive impact on customer share.